Pemberdayaan Masyarakat Melalui Kultur Jaringan Tanaman Hias Skala Rumah Tangga Pada Kelompok Tani Wulele Mowila di Kelurahan Wua-Wua Kendari - Arif, Norma; Bahari, Bahari (Amaliah: Jurnal Pengabdian Masyarakat, 2017)
Ornamental plant is prospective in Kendari Southeast Sulawesi. This market growth rapidly in the city so it may need to develope in large scale as quantity of a crop ornamental quality quite a lot and available at any time. The farmer’s Wulele Mowila (counterpart 1) and Sekar Merekah (counterpart 2) have developed business an ornamental in large scale. However, those farmers use a conventional approach, by this condition the group member were facing a problem to provide good quality of seeds. Hence, those problem are need a method of plant propagation ornamental new. One alternative was to culture techniques kultur in vitro. The purpose of the implementation of the program is to increase knowledge and skills of the farmers of both farmers in scale households, with laboratory the kultur that simple with a simple and practical method that had done by the farmers to produce seed an ornamental results of kultur in vitro, and bost enterprenur enthusiasm by forming network of partnerships between others. Methods is used by training and counseling and practice aproach which using laboratory scale households, sterilization tools and material for making simple medium and the implementation of the of copying seeds of ornamental plant, and also establishing network of partnerships between partner 1 and partner 2. The evaluation result shows that members of plant farmers have 80 % the participants increase their knowledge of the tissue culture plants scale households, and skilled in assemble and use laboratory, have skillful implement of principles work aseptic to make kultur in vitro equipment. In addition, 70 % members of the participants increased their knowledge and skill technique plant spreading of ornamental plant by kultur in vitro technic.